Recurrent Postmyocardial Infarction Ventricular Tachycardia: An Unusual Culprit - Akhil Kumar Sharma; Nirdesh Jain; Safal Safal; Vikas Kumar; Sudhanshu Kumar Dwivedi (Case Reports in Cardiology)
Although temporary transvenous pacing is life-saving in patients with myocardial infarction who develop bradyarrhythmias, the electrical complications resulting from it can be fatal and are rarely reported. We report here a patient with acute inferior wall myocardial infarction who required temporary transvenous pacing due to second-degree atrioventricular block accompanied with hypotension. Following coronary angiography and successful revascularisation, the patient developed multiple episodes of monomorphic and polymorphic ventricular tachycardia as well as ventricular fibrillation which on careful inspection were found to be initiated by fusion of the intrinsic and paced complexes. The problem of malignant ventricular tachycardia was solved by simple removal of the pacing lead. To the best of our knowledge, malignant ventricular tachycardia of both monomorphic and polymorphic types initiated by fusion complexes in a paced patient has not been reported in literature.